Telejornalismo sensacionalista e redução da maioridade penal: percepções de mulheres sobre direitos humanos e o adolescente em conflito com a lei - Trindade, Lívia do Amaral (2017)
This dissertation investigates whether sensationalist television journalism contributes to women being favorable to the reduction of the penal age in Brazil. Through the Multiple Mediation Theory (OROZCO, 2005), the process of receiving content from the Cidade Alerta and Cidade Alerta Goiás television channels is explored. As a starting point, 12 editions of these two newscasts are examinedto identify their sensational characteristics and the representation of the themes about the adolescent in conflict with the law, Statute of the Child and the Adolescent (ECA) and Human Rights. Then, drawing a parallel between the narrative of these television news, the perceptions of 24 women (12 viewers of these newsreels and 12 non-viewers) are analyzed. Of comprehensive interview (KAUFFMAN, 1993) and the technique of free association of words (BARDIN, 2011). Using elements of the Culture of Fear (GLASSNER, 2003) and Moral Panic (COHEN, 2002), the sensationalist television news programs collaborate in the construction of a social representation (MOSCOVICI, 1999) of adolescents in conflict with the law as unpunished and of the Statute Of the Child and Adolescent as an impediment to their accountability. There is a distorted representation on human rights, antagonistic to a perspective of otherness, in which they are considered an 'entity' that acts in the protection of those who should not integrate society, among them adolescents who commit an infraction. This narrative is identified both in these news releases, and in the interviewees' speeches. The representation of the adolescent above the law is verified both in the viewers and in the other participants of the research. Even those who do not watch primarily sensationalist newscasts cite memories related to facts shown by television news outlets to certify their opinions - in cases that have been thoroughly exploited by the media (including sensationalist approaches). The greater the level of credibility of the television news, the greater its possibility of contribution in the formation of opinion. For those who watch the Cidade Alerta and Cidade Alerta Goiás, ‘the truth’ is the basis of these news programs.